Understanding Flavivirus Capsid Protein Functions: The Tip of the Iceberg - Stephanea Sotcheff; Andrew Routh (Pathogens, 2020)
Flaviviruses are enveloped positive-sense single-stranded RNA arboviruses, infectious to humans and many other animals and are transmitted primarily via tick or mosquito vectors. Capsid is the primary structural protein to interact with viral genome within virus particles and is therefore necessary for efficient packaging. However, in cells, capsid interacts with many proteins and nucleic acids and we are only beginning to understand the broad range of functions of flaviviral capsids. It is known that capsid dimers interact with the membrane of lipid droplets, aiding in both viral packaging and storage of capsid prior to packaging. However, capsid dimers can bind a range of nucleic acid templates in vitro, and likely interact with a range of targets during the flavivirus lifecycle. Capsid may interact with host RNAs, resulting in altered RNA splicing and RNA transcription. Capsid may also bind short interfering-RNAs and has been proposed to sequester these species to protect flaviviruses from the invertebrate siRNA pathways. Capsid can also be found in the nucleolus, where it wreaks havoc on ribosome biogenesis. Here we review flavivirus capsid structure, nucleic acid interactions and how these give rise to multiple functions. We also discuss how these features might be exploited either in the design of effective antivirals or novel vaccine strategies.